The South China Sea disputes flashpoints, turning points, and trajectories - Yang Razali Kassim (World Scientific, 2017)
The book is divided into four sections, taking off from a key diplomatic or related incident/development which can be seen as a turning point for each, with the concluding section looking at what lies ahead for Southeast Asia and the larger Asia-Pacific region, amidst the uncertainties triggered by the South China Sea imbroglio.